Implementation of the user-centered design (UCD) method for designing web marketplace of qurban cattle sales in Indonesia - Rahmawati, Endra (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2020)
This study aims to create a user interface design for the designing web marketplace of qurban cattle sales in East Java, Indonesia. The word qurban referred asÂ the qurban animal slaughtered during the Eid al-Adha, especially cow.Â The qurban web market can help breeders and customers in the process of selling cattle directly without limited territory.Â This is because the process of selling qurban cows is still done traditionally by ordering directly by phone and coming directly to the cattle pen for the selection of qurban animals desired by consumers. To deal with these problems, an alternative solution is needed that can create a Web Marketplace interface design that is designed using the User-Centered Design (UCD) method, focusing on the user's primary needs. This method was chosen because it focuses on the user's goals, characteristics, and workflow in the design process. How the system can be understood and used by users is a top priority in this web design and involves users in designing the marketplace web interface. Therefore it is very suitable for designing a website that is simple and easy to use. The design of the web marketplace of qurban cattle sales has four main features which are promotion of qurban cattle, online qurban cattle bookigs (direct purchases or livestock care services), payment confirmation, and qurban cattle contributions for collective purchases or in groups. The results of the System Usability Scale (SUS) test distributed to 30 respondents obtained a value of 79.3 which indicates that the qurban web marketplace design can be accepted by users and can be classified as good design.